Odpowiedzi

Najlepsza Odpowiedź!
2010-01-03T15:02:40+01:00
A)
1/3 y = x-3
y=3x-9

3(x-y) = 2x
3x-3y=2x
-3y=2x-3x
-3y=-x
y=1/3x

2/3x = 3/4y
3/4y=2/3x
y=8/9x

b)
1/3 y = x-3
x-3=1/3y
x=1/3y+3

3(x-y) = 2x
3x-3y=2x
x=3y

2/3x = 3/4y
x=9/8y
3 3 3
2010-01-03T15:05:11+01:00
A)
1/3 y = x-3 |:(1/3)
y=(x-3):1/3
y=(x-3)*3
y=3x-9

3(x-y) = 2x |:3
x-y=2x/3
-y=(2x/3)-3
-y= (2x-9)/3 |:(-1)
y= (9-2x)/3

2/3x = 3/4y |:(3/4)
(2/3 *x):3/4=y
2x*4/3*3 = y
y= 8x/9

b) Z równań podnanych w zadaniu 2 wyznacz x.

y=3x-9
3x=y+9 |:3
x= (y+9)/3

y= (9-2x)/3 |*3
3y=9-2x
3y-9=-2x |:(-2)
x= -(3/2)*y - 4,5

y= 8x/9 |:9
9y=8x |:8
x=(9/8)x
1 5 1